2015
DOI: 10.1111/age.12306
|View full text |Cite
|
Sign up to set email alerts
|

Association study of single nucleotide polymorphisms inJAK2andSTAT5Bgenes and their differential mRNA expression with mastitis susceptibility in Chinese Holstein cattle

Abstract: The JAK-STAT pathway plays a key role in mediating immune responses. The genetic effects of single nucleotide polymorphisms (SNPs) in JAK2 and STAT5B were investigated for serum cytokines, mastitis indicators and productions traits in a population of 468 Chinese Holstein cattle. Pooled DNA sequencing revealed one SNP (BTA8:g.39645396A>G) in JAK2 and two SNPs (BTA19:g.43673888A>G and BTA19:g.43660093T>C) in STAT5B. A fixed effect model considering the effects of SNPs, parity, herd, season and year of calving wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 42 publications
(45 reference statements)
0
29
0
Order By: Relevance
“…In the PI3K pathway AKT isotopes are the crucial signaling molecules which regulate cell growth, proliferation, survival, and metabolism [ 13 ]. For tackling diseases, their immunity related functions are important [ 38 , 39 ]. AKT is also involved in the regulation of inflammatory cytokines with proinflammatory property as shown in the TLR signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…In the PI3K pathway AKT isotopes are the crucial signaling molecules which regulate cell growth, proliferation, survival, and metabolism [ 13 ]. For tackling diseases, their immunity related functions are important [ 38 , 39 ]. AKT is also involved in the regulation of inflammatory cytokines with proinflammatory property as shown in the TLR signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…However, AKT1, as a key player in the Jak2/STAT5 pathway, plays an important role in the regulation of differentiation, secretion, survival, and proliferation of mammary epithelial cells as well as mammary remodeling and lactation sustainability in dairy cows (90, 97100). JAK2 and STAT5, two key players in the immune response, are associated with cow mastitis susceptibility (11, 101). Mastitis caused by bacterial infection of the mammary gland induces IL8 expression (102), and IL-8 plays an important role in the recruitment and degranulation of neutrophils in mammary gland (13).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings demonstrated that SNPs at locus 39652267C/T and 39645396C/T in JAK2 had a significant association with milk fat percentage. However, previously, our research group did not find any link of these SNPs in JAK2 with milk production traits, including milk fat percentage (Usman et al ., 2014, 2015). In exon 16 of JAK2, phosphorylation occurs at 39652267A/G which affects the STAT gene that regulates the transcription of different genes in the nucleus and plays a key role in varieties of processes (Szewczuk, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Cytokine-based marker-assisted selection could allow progress toward mastitis resistance and improvement in milk production traits. In the present study, we selected the SNPs in JAK2 from previous studies of our research team (Usman et al ., 2014, 2015) due to its key role in mastitis resistance. The DGAT1 has widely been studied and reported for its role in milk production traits in dairy cattle (Grisart et al ., 2004; Schennink et al ., 2007; Yuan et al ., 2007; Molee et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%